A Novel Method for Calculating Approximate Weight of an Object through its Image - Meher, Amaresh Chandra; Singh, Uddgam; Senapati, Kishore Kumar (Transactions on Engineering and Computing Sciences, 2015)
The field of computer science is capable of calculating approximate weight of an object through its image. It is new and challenging. The idea behind the weight of an object is nothing but approximation of the pixel carries some weight value which is specific for the corresponding specific object. It is a challenge for the computer science people to develop methods through pixel weight. The main focus of this paper is to find the approximate weight of an object through its digital image. Generally weight calculating machine is used to find out the weight of any object(s). To improve the process and to make it somehow digitized we have proposed a novel method that does not require any physical standard to calculate weight. Initially, a surface image is captured by the system and whenever a newly taken image, i.e., the image of object placed over the same surface is input, it will be subtracted from our pre-existing surface image. Based on the features of colour attribute the weight of the object is estimated. From the experimental results, it is observed that the proposed model works perfectly on both training data as well as novel data. We believe this paper could form a base for future works on related topics.